Pragmatism and activity theory: Is Dewey’s philosophy a philosophy of cultural retooling? - Miettinen, Reijo (Outlines. Critical Practice Studies, 2006)
A philosopher of education, Jim Garrison, has suggested that John Dewey’s philosophy is a philosophy of cultural retooling and that Dewey adopted both his conception of work and the idea of tool as "a middle term between subject and object” from Hegel. This interpretation raises the question of what the relationship of the idea of cultural retooling in Dewey’s work is to his naturalism and to his allegiance to Darwinian biological functionalism. To deal with this problem, this paper analyzes how the idea of cultural retooling is elaborated in Dewey’s logic and in his theory of reflective thinking and compares it to the concept of retooling in Vygotsky and activity theory. Dewey does recognize the significance of tools in human practice and the role of language in the formation of meaning. However, in his theory of thinking and problem solving, he primarily resorts to the biological or ecological language of the organism–environment, in which the concepts of habit and situation play a central role. It is argued that this language does not deal with the functions and relationships of different kinds of tools and artifacts in changes of activity nor supply satisfactory means of analyzing the historical, institutionalized and cultural dimensions of human activity.